A study to assess the impact of maternal psycho-emotional health on childhood morbidity: a comparative study of ART and natural conception - Iskakova, Aiman; Manzhuova, Lyazat; Iskakova, Gulnara; Assulkanova, Nazgul; Nusipzhanova, Kulzhamila (Acta Biomedica Atenei Parmensis, 2024)
The aim of this study was a longitudinal study to assess the impact of the psycho-emotional state of health of 252 mothers and the level of maternal care on the morbidity rate of acute respiratory infections in children born using assisted reproductive technologies (ART) and by natural conception.  In addition, the effects of prematurity and low birth weight, Apgar scores, breastfeeding, and kindergarten attendance on the incidence of acute upper and lower respiratory tract infections in children in both groups were studied. We compared two comparable groups of healthy children aged 0- to 3 years and their mothers. The mothers' levels of anxiety and depression were determined, as well as the level of parental care for the child, and a personal interview was also conducted.  The children were examined, as well as a history and analysis of medical records. Univariate and multivariate negative binomial regression analysis models were used for statistical analysis to assess the influence of predictors on child morbidity rates. The incidence of respiratory tract infections was significantly lower in the ART group. As a result of the study, we did not find a statistically significant effect of maternal anxiety and depression on the incidence of respiratory infections in their children in both groups. Our findings revealed that after the birth of a child, mothers in the ART group took better care of the long-awaited and often only child, which reduced the incidence of the disease in this group.